Analisis Pengaruh Ukuran Perusahaan, Leverage, Profitabilitas, dan Intensitas Modal terhadap Penghindaran Pajak pada Perusahaan yang Terdaftar di Bursa Efek Indonesia - Robby Krisyadi; Efri Mulfandi (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2021)
Abstrak The research was conducted to test and analyze the independent variables against the dependent variable. The independent variable consists of company size, leverage, profitability, and capital intensity and the dependent variable is company tax avoidance. The object of this research is a company that has an annual report that is registered and published on the Indonesia Stock Exchange for the period 2015-2019. The sample selected based on purposive sampling technique of 452 companies. The data is then processed with SPSS and Eviews software, which are analyzed using panel regression models. The results obtained by researchers indicate that company size and tax avoidance have a significant positive relationship. Leverage, profitability, and capital intensity variables do not show a significant relationship to tax avoidance.